A comprehensive in silico investigation into the pathogenic SNPs in RTEL1 gene and their biological consequences - Tanshee, Rifah Rownak (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.